Albania Urban Sector Review - World Bank (Washington, DC, 2014)
This report on Albania urban sector review focuses on trends and issues that have come to the fore with rapid urbanization and with the recent decentralization of major responsibilities to local governments. Continuing the achievements and addressing the problems will require actions by local governments and, just as importantly, by the central government, which sets the legal and regulatory conditions for local governance and the tone of political leadership. The major challenges facing both levels of government include: 1) restoring a better balance between public goods and private goods, and between public interests and private interests, as demonstrated in urban management and land use; 2) devising and implementing a form of urban planning and regulation that serves the urban economy and the demands for commercial and household real estate, and can be enforced; 3) making local governments more effective managers of cities, with sustainable financing. This implies that the private sector is enabled and not hampered by avoidable problems with local infrastructure services, or by unnecessary regulations or fiscal impositions; and 4) helping the citizens who remain relatively disadvantaged to continue improving their welfare, including their housing assets, in the urban location. The study concludes that the dramatic transformations Albania has experienced since the transition have had very clear spatial dimensions. The increased concentrations of population settlement and of economic activity have brought about improvements in welfare for both the urban residents and for the communities sending migrants. The geographic pattern of Albania's economy is strong and apparently becoming more established, as the Tirana/Durres metropolitan region will likely remain the economic center of gravity. Urban growth will continue but at a measured pace, as Albania's urbanization rate approaches levels seen elsewhere in Europe. National development strategies and policies, including policies to strengthen and improve the investment climate experienced by firms in each city, should therefore acknowledge and work with these spatial realities.